Anthropogenic carbon and water masses in the Bay of Biscay - Castano-Carrera, M; Pardo, PC; Alvarez, M; Lavin, A; Rodriguez, C; Carballo, R; Rios, AF; Perez, FF (2012)
As part of the VACLAN (Climate Variability in the North Atlantic) project, a section covering the Bay of Biscay was sampled in September 2005. This work estimates the distribution of the different water masses in the region using an extended optimum multiparametric method and analyzes water mass distribution of anthropogenic carbon as calculated using two different approaches. The Eastern North Atlantic Central Water layer is mainly constituted by its subpolar component and Mediterranean Water appears very diluted, its dilution increasing northeastward. In relation to the anthropogenic carbon inventory, small differences were found between the two different methods used, 95 vs 87 mol C m–2, though both show the same distribution pattern, the concentration decreasing with depth. Eastern North Atlantic Central Water presents the highest anthropogenic carbon inventory, supporting more than 50% of the total column (52%). This work confirms the relevant role of the Bay of Biscay as a sink zone in the oceanic circulation.